For whom the trains roll? An equity analysis of rail enhancement in Israel - Rotem-Mindali, Orit; Feitelson, Eran; Michael, Yaron (Frontiers in Sustainable Cities, 2025)
Rail has enjoyed somewhat of a renaissance in recent decades, with substantial new investments made therein. Justification oftentimes rests on rail’s non-transport benefits, particularly the idea of opening-up new prospects for the carless. While many studies focus on accessibility to opportunities, this study attempts to evaluate the equity of investments. To that end, it is particularly pertinent to assess the degree to which rail is accessible to the carless, to identify exactly who benefits from the investment in rail, and who does not. As inter-city rail is inherently spatially inequitable, feeder bus services are sometimes added to mitigate these inequities. In this paper, we analyzed the equity facets of the enhancement of inter-city rail, including feeder bus services, in Israel, by examining the siting of rail stations, and mapping out all bus routes reaching heavy rail stations nationwide. Subsequently, we analyzed the attributes of the cities and towns serviced by rail, and of the population residing near bus stops on the feeder routes, as well as the frequency of service in those stops. Access to inter-urban rail in Israel was investigated, in terms of equity, at an unprecedented level of detail, thereby enabling us to assess which population groups stand to potentially benefit from the very substantial current investments in rail. We found that the Arab minority benefits the least, with adverse implications on women’s motility, largely due to limited bus feeder lines to the rail system.